Diffusion Analysis of Innovation in the Implementation of Hygiene Programs: A Case Study of the Bangkalan Initiative - Dawam, Aulia; Subroto, Waspodo Tjipto; Sakti, Norida Canda (Formosa Journal of Science and Technology, 2025)
This study aims to analyze the process of diffusion of innovation in the implementation of hygiene programs in Bangkalan Regency, to understand how hygiene innovations are accepted and adopted by the local community as well as the challenges faced in the cleanliness program implemented by the Bangkalan Initiative Community, to find out how much influence the success and failure of diffusion of hygiene innovations, including public awareness, limitations of infrastructure,  and participation in environmental cleanliness programs. This study uses a descriptive method with a qualitative research type. The types and sources of information used in this study are using 2 types, namely primary data and secondary data. Initial information obtained from the first source of information or field hands, then we obtained this secondary information based on observations from podcasts along with documentation on Bangkalan social media initiatives such as: YouTobe, Instagram, and Tik Tok. The results of the study show that although there are a number of efforts to increase public awareness and provide hygiene facilities, the low level of community participation and limited human resources (HR) are still the main obstacles. Therefore, a more interactive innovation diffusion strategy that involves direct community participation in each stage of the program is urgently needed to increase the effectiveness and reach the cleanliness program in Bangkalan. This study provides recommendations for improvements in the design and implementation of a more inclusive and sustainable hygiene program. The Bangkalan program initiative has a great impact in the field of cleanliness, especially the Bangkalan community. The first step in the process of diffusion of innovation in the Bangkalan cleanliness initiative is the role of education, especially educators, which is the main factor.